Dual growth factor-immobilized bioactive injection material for enhanced treatment of glottal insufficiency. (1st March 2019) - Choi, Young Hwan; Ahn, Hee-Jin; Park, Mi Ri; Han, Mi-Jung; Lee, Jin Ho; Kwon, Seong Keun
Graphical abstract: Abstract: With increasing demand for treatment of glottal insufficiency, several injection materials have been examined. However, biological resorption, degradation of injected materials, and the subsequent need to perform multiple injections still remain major clinical problems. In this study, we fabricated two different growth factor (GF) [single basic fibroblast growth factor (bFGF), single hepatocyte growth factor (HGF), or dual bFGF/HGF]-immobilized polycaprolactone (PCL)/Pluronic F127 microspheres. These materials were investigated for their potential use as bioactive injection laryngoplasty agents. HGF was found to be continuously released over 20 days and the bFGF was found to be continuously released over 25 days, as demonstrated by ELISA assay. Human vocal fold fibroblasts (hVFFs) showed significantly higher proliferative ability on dual GF-immobilized microspheres. GF-immobilized microspheres (bFGF, HGF, and dual GF) were injected into paralyzed vocal folds of New Zealand white rabbits. Through endoscopic observation and H&E staining, we identified that the microspheres remained localized at the injection site, resulting in constant volume augmentation of the paralyzed vocal fold without significant loss of the initial volume after 4 weeks. The expression of genes related to the extracellular matrix (ECM) in the vocal fold was upregulated by dual GF-immobilized microspheres. Furthermore, dual GF-immobilized microspheres inhibited muscle degeneration and upregulation of myogenic-related genes. In conclusion, dual GF-immobilized microspheres passively augmented the volume of the paralyzed vocal fold while actively inducing ECM synthesis at the injected vocal fold and preserving muscle tissue. Dual GF-immobilized microspheres could be a new and promising injection material for paralyzed vocal folds. Statement of Significance: Limitation of prolonged augmentation of vocal fold and degeneration of vocal fold tissue still remain as major clinical problems in the treatment of vocal fold paralysis. Herein, we fabricated the polycaprolactone (PCL)/Pluronic F127 microspheres to augment volume of paralyzed vocal folds. On top of that, we additionally immobilized the growth factors (bFGF, HGF, or dual bFGF/HGF) on the surface of these microspheres. We highlight the efficacy of the dual GF-immobilized microspheres which augmented the volume of the paralyzed vocal fold passively, induced ECM synthesis actively at the injected vocal fold and preserved laryngeal muscle tissue. Our results suggest that the dual GF-immobilized microsphere could be a new promising injection material for injection laryngoplasty to treat paralyzed vocal fold.